2014
DOI: 10.1007/s00464-014-4046-0
|View full text |Cite
|
Sign up to set email alerts
|

Variation of outcome and charges in operative management for diverticulitis

Abstract: Patients who undergo surgical treatment for diverticulitis in the United States have high geographic variation in mortality, LOS, and hospital charges despite adjusting for demographic and socioeconomic factors. Further analysis should be performed to identify the causes of outlier regions, with the goal of improving and standardizing best practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 29 publications
0
16
1
Order By: Relevance
“…The CCI is associated with an increase in AD-related mortality and recurrence rate. 28,29 Instead in our study, we found a progressive reduction of CCI score in the observed period, mainly in the uncomplicated form of diverticulitis. This could be explained by the reduction in the mean age of patients at admission.…”
Section: Discussioncontrasting
confidence: 63%
“…The CCI is associated with an increase in AD-related mortality and recurrence rate. 28,29 Instead in our study, we found a progressive reduction of CCI score in the observed period, mainly in the uncomplicated form of diverticulitis. This could be explained by the reduction in the mean age of patients at admission.…”
Section: Discussioncontrasting
confidence: 63%
“…After being assessed for the availability of data for indigenous vs nonindigenous populations, 80 articles were subsequently removed. Following bibliography scans, contact with international experts, and gray literature search, an additional 9 articles and 7 reports were added, leaving a total of 21 articles [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]42,44 and 7 reports 14,[45][46][47][48][49][50] from 27 studies for data extraction.…”
Section: Resultsmentioning
confidence: 99%
“…Meta-data for all included studies are presented in Table 2. Of 21 articles, 11 studies were conducted in the US, [26][27][28][29]31,[35][36][37][38]42,51 7 in Australia, 25,30,33,34,39,40,44 and 2 in New Zealand. 32,43 All were cohort studies, with 17 retrospective studies 25,[28][29][30][31][32][33][35][36][37][38][39][41][42][43][44]51 and3prospective studies (from 4 articles).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Outcome variation between regions, health networks and individual centres has been demonstrated internationally across many procedures, including pancreaticoduodenectomy (PD). A national USA study confirmed a significant geographical variation in mortality for patients undergoing surgical management of diverticulitis despite adjustment for demographic and socio‐economic factors . Furthermore, two USA studies investigating colonic resection for malignancy determined significant variation in risk standardized in‐hospital mortality rates across the nation .…”
Section: Introductionmentioning
confidence: 99%
“…A national USA study confirmed a significant geographical variation in mortality for patients undergoing surgical management of diverticulitis despite adjustment for demographic and socioeconomic factors. 2 Furthermore, two USA studies investigating colonic resection for malignancy determined significant variation in risk standardized in-hospital mortality rates across the nation. 9,10 Analysis demonstrated five hospital networks to have significantly higher risk adjusted 30-day post-operative mortality compared with others across England.…”
Section: Introductionmentioning
confidence: 99%